Incremental cooperative spectrum sensing algorithm with n-out-of-K fusion rule - Xiao-ge ZHANG; Shi-bing ZHANG; Gong-an QIU (Tongxin xuebao)
The algorithm divided the total relays into two subsections.The front subsection included N number of relays,and the later one included K−N number of relays.Firstly,the front N relays sensed the spectrum.If no more than mL number of relays had detected the existing of the primary user,the global detection was that the spectrum holes existed.If more than mH number of relays had detected the existing of the primary user,the global detection was that no spectrum holes existed.Otherwise,the later K−N number of relays continued to sense the spectrum.The global detection was that the spectrum holes existed only when there were totally over n number of relays having detected the existing of the primary user in the two sensing stages.The object function was built for minimizing the time-slot consumption by adjusting the parameters mL,mH and N with the limit of detection probability and false probability.Simulation results show that the proposed incremental cooperative spectrum sensing algorithm has much lower time-slot consumption than the traditional one by properly setting the parameters with high sensing performance kept.